Estudo ergonômico dos postos de trabalho do setor de pesagem de uma indústria de calçados: estudo de caso - Cunha, Francisco Aleudiney Monte (2007)
The world in constant change, the globalization economy and of emergent markets, modern managemental technologies have oportunizado considerable improvements in the form of as the companies can become highly competitive and get considerable profits of productivity. Such situations are provoked by the necessity that the companies have to be competitive, productive and prompt in the delivery stated periods, as form of survival in the market. Usually, the company Grendene S/A does not run away from this profile, explained for its transport and reputation in the market. The work in the ranks of work of the sector of Pesagem in Unit 4 of Grendene S/A is ergonomicamente correct? This work has the objective of raising and pointing certain situations that, although to have intention to become the lucrative companies most agile and, finish causing resulted contrary, since such actions compromise the health and the performance of the workers in average stated period. Carrying through ergonomic study of the ranks of work of the sector of Pesagem of Unit 4 of Grendene S/A. The study it was descriptive exploration with qualitative boarding, that if used the mapping, description and analysis of the context, the relations and perceptions regarding the situation of ergonomics in the company, using as procedure methodological the study of case for making direct comment of the phenomenon. No was carried through in the area of Pesagem of the Plant of compostagem of PVC of Grendene S/A, characterized for the system of taylorista-fordista production sector worked 06(six) load weighers, 02(two) suppliers, 01(one) estoquista and 01(one) person in charge, beyond the leader. The elements had been analyzed all that composed the activities, the exercises if they repeat in each existing function in the sector and focused the movement, the frequency, the time and the positions practised during the work. Photos, systematic filmings, comments for each activity developed for the workers had been used. E analyzed the same ones of the biomechanic point of view, with the use of the equation of the NIOSH for manual load survey to verify the existence of risks. Proposals of measures of control for the activities had been raised that if they had shown inadequate. Having as resulted the existing functions in the pesagem sector, one really evidenced that the activities of Leader, estoquista and supplier, did not offer no ergonomic risk. To the step that the function of the Load Weigher, deserves intervention, although not to reach the maximum level of risk according to equation of the NIOSH. In the function Weigher several are the claims for the exercise of the activity; the non-availability for hourextra is a reality. The company has oscillations in the volumes of production due to sazonalidade in venda of footwear, and this reflects directly in the PVC production. In the sector of Pesagem two collaborators exist practising hidroginástica for medical orientation, being very common to the claims of pains in the coasts. We have as conclusion the challenge to adopt among others of one practical ergonomic that considers, lines of direction, the qualification of professionals, mainly of the load weigher for the precocious diagnosis of the ergonomic work